THE THE CORRELATION BETWEEN READING HABITS AND READING COMPREHENSION OF ELEVENTH GRADE STUDENTS AT MADRASAH ALIYAH AT-TAHZIB - Elmafitria, Jazila; Zamzam, Ahmad; Thohir, Lalu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the correlation between students’ reading habits and their reading comprehension at Madrasah Aliyah At-Tahzib. The problem addressed is students’ low reading comprehension, which is influenced by limited reading practice, lack of vocabulary, and low motivation in reading activities. This study aims to determine whether there is a significant correlation between reading habits and reading comprehension among eleventh grade students. This research employed a quantitative correlational design with an ex post facto approach. Data were collected using a reading habits questionnaire and a reading comprehension test, and were analyzed using the Pearson Product-Moment correlation. The results showed a correlation coefficient of r = .399 with a significance value of .006, indicating a positive and significant correlation between reading habits and reading comprehension, although the level of correlation is considered low.